Absence of phylogenetic signal in the niche structure of meadow plant communities - Silvertown, Jonathan (The Royal Society, 2005)
A significant proportion of the global diversity of flowering plants has evolved in recent geological time, probably through adaptive radiation into new niches. However, rapid evolution is at odds with recent research which has suggested that plant ecological traits, including the β- (or habitat) niche, evolve only slowly. We have quantified traits that determine within-habitat α diversity (α niches) in two communities in which species segregate on hydrological gradients. Molecular phylogenetic analysis of these data shows practically no evidence of a correlation between the ecological and evolutionary distances separating species, indicating that hydrological α niches are evolutionarily labile. We propose that contrasting patterns of evolutionary conservatism for α- and β-niches is a general phenomenon necessitated by the hierarchical filtering of species during community assembly. This determines that species must have similar β niches in order to occupy the same habitat, but different α niches in order to coexist.